Ongoing outbreak of dengue serotype-3 in Solomon Islands, January to May 2013 - Francisco Nogareda; Cynthia Joshua; Alison Sio; Matthew Shortus; Tenneth Dalipanda; Kara Durski; Jennie Musto; Elliot Puiahi; Alfred Dofai; John Aaskov; Van Mai Cao-Lormeau; Didier Musso; et al. (World Health Organization Regional Office for the Western Pacific, 2013)
Introduction: In January 2013, clinicians in Honiara, Solomon Islands noted several patients presenting with dengue-like illness. Serum from three cases tested positive for dengue by rapid diagnostic test. Subsequent increases in cases were reported, and the outbreak was confirmed as being dengue serotype-3 by further laboratory tests. This report describes the ongoing outbreak investigation, findings and response. Methods: Enhanced dengue surveillance was implemented in the capital, Honiara, and in the provinces. This included training health staff on dengue case definitions, data collection and reporting. Vector surveillance was also conducted. Results: From 3 January to 15 May 2013, 5254 cases of suspected dengue were reported (101.8 per 10 000 population), including 401 hospitalizations and six deaths. The median age of cases was 20 years (range zero to 90), and 86% were reported from Honiara. Both Aedes aegyti and Aedes albopictus were identified in Honiara. Outbreak response measures included clinical training seminars, vector control activities, implementation of diagnostic and case management protocols and a public communication campaign. Discussion: This was the first large dengue outbreak documented in Solomon Islands. Factors that may have contributed to this outbreak include a largely susceptible population, the presence of a highly efficient dengue vector in Honiara, a high-density human population with numerous breeding sites and favourable weather conditions for mosquito proliferation. Although the number of cases has plateaued since 1 April, continued enhanced nationwide surveillance and response activities are necessary.